2017
DOI: 10.1007/s10875-017-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Adult Patients with Common Variable Immunodeficiency Disorders and Impact of Treatment

Abstract: PurposeCommon variable immunodeficiency disorder (CVID) is a primary immunodeficiency disease (PIDD) often associated with severe and chronic infections. Patients commonly receive immunoglobulin (Ig) treatment to reduce the cycle of recurrent infection and improve physical functioning. However, how Ig treatment in CVID affects quality of life (QOL) has not been thoroughly evaluated. The purpose of a recent Immune Deficiency Foundation (IDF) mail survey was to assess the factors that are associated with QOL in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 41 publications
2
53
2
Order By: Relevance
“…As reported previously [7], 4000 surveys were mailed and 1608 were received. A second mailing to non-respondents was conducted on 27 January 2014.…”
Section: Survey Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously [7], 4000 surveys were mailed and 1608 were received. A second mailing to non-respondents was conducted on 27 January 2014.…”
Section: Survey Subjectsmentioning
confidence: 99%
“…Infections are a hallmark of immune abnormality, and their incidence has been correlated inversely with QoL [7]. Thus, we evaluated the association between fatigue and infection frequency.…”
Section: Relationship Between Medical Variables and Fatiguementioning
confidence: 99%
“…Previous studies have shown that there are subgroups of patients with CVID with respect to their genotype, B cell or T cell profiles and clinical phenotypes [10][11][12][13][14][15][16]. In contrast to previous studies on HRQoL [2,21,22], we were able to analyze it according to the patterns of physical and mental health scores. As has been shown for other chronic diseases, patients are not usually a homogeneous group [17][18][19], but differ according to medical situation, social and psychological support and resilience.…”
Section: Introductionmentioning
confidence: 89%
“…Perceived health as a subjective measure of general health of individuals is a significant predictor of a number of outcomes, such as recovery from illness, greater satisfaction with care, physicians' ratings of health status, new morbidity and health-care utilization [1,2]. It is also an important predictor of mortality [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation